Trabeculectomy with intraoperative retrobulbar triamcinolone acetonide - Kahook, Malik Y (Dove Medical Press, 2009)
Use of topical steroids is an important component of postoperative care after filtration surgery. Efficacy of postoperative medications is affected by patient adherence and physical limitations in the elderly population often prohibit proper dosing of ophthalmic drops. We describe a technique for the use of intraoperative retrobulbar triamcinolone acetonide in trabeculectomy surgery and report on postoperative outcomes. This technique appears safe and may be an attractive method of delivering a steroid depot at the time of trabeculectomy.